The Therapeutic Potential of Novel Kappa Opioid Receptor-based Treatments - Mercadante, Sebastiano; Romualdi, Patrizia (Current Medicinal Chemistry, 2020)
Introduction: Similarly to the μ opioid receptor, kappa opioid receptor (KOR), is present either in the central nervous system or in peripheral tissues. In the last years, several molecules, able to interact with KOR, have been the focus of basic research for their therapeutic potential in the field of chronic pain, as well as in depression, autoimmune disorders and neurological diseases. Discussion: The role of KOR system and the consequent clinical effects derived by its activation or inhibition are discussed. Their potential therapeutic utilization in conditions of stress and drug relapse, besides chronic pain, is presented here, including the possible use of KORagonists in drug addiction. Moreover, the potential role of KOR-antagonists, KOR agonistantagonists and peripheral KOR agonists is proposed. Conclusion: Other than pain, KORs have a role in regulating reward and mood. Due to its location, KORs seem to mediate interactions between psychiatric disorders, addiction and depression. Experimental studies in animal models have identified brain mechanisms that may contribute to clarify specific pathophysiological processes.
Keywords: drug